2022
DOI: 10.1155/2022/4432977
|View full text |Cite
|
Sign up to set email alerts
|

How Travel Vlogs on YouTube Influence Consumer Behavior: A Use and Gratification Perspective and Customer Engagement

Abstract: YouTube is one of the emerging technologies that impact consumer behavior. In the tourism sector, travel video blogs (travel vlogs) have become increasingly popular since they are highly influential in influencing travel behavior. Similarly, YouTube travel vlogs are highly engaging and provide consumers with destination experiences. This study determines how consumer behavior expressed through emerging technologies, such as travel vlogs on YouTube, can influence travel intention and electronic-Word of Mouth (e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 100 publications
1
9
0
Order By: Relevance
“…This may indicate that the higher the quality of online word of mouth reviews, the stronger the consumers' sense of product quality, accelerating consumers' decision-making behaviors. This is consistent with the findings of Nieto-García et al ( 2017), Pourfakhimi et al (2020), and Silaban et al (2022), and also verifies that the quantity of online word of mouth evaluations can positively and directly affect tourists' travel intentions, which is consistent with the conclusion of Wei (2020) and Xu and Yao (2020). Hypotheses H4a and H4b on whether there is a mediating effect for online word of mouth on a destination's cognitive image and tourists' travel intentions have been verified.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This may indicate that the higher the quality of online word of mouth reviews, the stronger the consumers' sense of product quality, accelerating consumers' decision-making behaviors. This is consistent with the findings of Nieto-García et al ( 2017), Pourfakhimi et al (2020), and Silaban et al (2022), and also verifies that the quantity of online word of mouth evaluations can positively and directly affect tourists' travel intentions, which is consistent with the conclusion of Wei (2020) and Xu and Yao (2020). Hypotheses H4a and H4b on whether there is a mediating effect for online word of mouth on a destination's cognitive image and tourists' travel intentions have been verified.…”
Section: Discussionsupporting
confidence: 92%
“…For example, Adeloye et al (2021) found that vlogs can significantly impact tourist travel intentions. Silaban et al (2022) argued that watching travel vlogs on YouTube can significantly affect consumers’ travel intentions. In terms of the ways in which the image of a tourist destination generated by videos can significantly and positively motivate tourists to visit ( Fu et al, 2016 ; Li et al, 2021 ).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…This study collected respondent data using a Google Forms questionnaire distributed randomly through social media platforms (e.g., Instagram, WhatsApp, and Facebook). Previous studies also used the same data collection procedure [64,65].…”
Section: Sampling Technique and Data Collectionmentioning
confidence: 99%
“…The Uses and Gratification (U&GT) Theory is used to explain the individual's motivation and satisfaction towards social and psychological needs (Dolan et al, 2019;Silaban et al, 2022). U&GT allows the present study to investigate why tourists are satisfied with their staycation in a tourist destination.…”
Section: Gratification Of Wellness Tourismmentioning
confidence: 99%